A Three-Dimensional Dual-Band Terahertz Perfect Absorber as a Highly Sensitive Sensor - Yin, Wei; Shen, Zhonglei; Li, Shengnan; Zhang, Liuyang; Chen, Xuefeng (Frontiers in Physics, 2021)
Terahertz (THz) absorbers are highly desirable in sensing and detection devices. Herein, we have proposed a dual-band near-perfect absorber that works in the terahertz regime for the sensing application. The theoretical calculation shows that the absorption efficiency of the absorber can reach 99.0% and 97.0% at 1.125 THz and 1.626 THz, respectively. Double two absorption peaks can be tuned independently by alternating the geometric parameters of unit resonators. The underlying physical mechanism of the absorber matches well with the well-known impedance matching theory. Compared with its planar counterpart, our proposed absorber exhibits at least two times figure of merit enhancement due to its out-of-plane induced large interfacial area. Additionally, the absorber can work robustly at a wide range of incident angles and keep insensitive to polarization states, which renders it great potential for highly sensitive sensing.